2018
DOI: 10.1016/j.jare.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Is arachidonic acid an endoschistosomicide?

Abstract: Graphical abstractArachidonic acid interacts with the surface double lipid bilayer shield of larval, developing and adult schistosomes, leading to its disintegration and eventual parasite attrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…It is because PUFAs, and not saturated fatty acids, that function as endogenous antimicrobial molecules (45). The results together suggest S. haematobium, known for their higher sensitivity to PUFAs (9,10,21,41)…”
Section: Arachidonic Acid Is Endoschistosomicidal In the Intermediatementioning
confidence: 87%
“…It is because PUFAs, and not saturated fatty acids, that function as endogenous antimicrobial molecules (45). The results together suggest S. haematobium, known for their higher sensitivity to PUFAs (9,10,21,41)…”
Section: Arachidonic Acid Is Endoschistosomicidal In the Intermediatementioning
confidence: 87%
“…In support of this hypothesis, papain injection skewed innate and acquired immune responses to the antigens of invading S. mansoni towards the type 2 axis, preceding the effects of egg-derived soluble antigens, with preponderance of IgG1 antibodies and accumulation of uric acid and ARA in the lung 7 days PI and in the liver starting 17 days PI. Type 2-related antibodies to ESP, especially cysteine peptidases, and ARA, a documented schistosomicide [42], [43], [44], [45] and a putative endoschistosomicide [21], [22], [23], appear to join forces to mediate the attrition of developing worms in the lung capillaries and liver sinusoids. Repeat experiments have demonstrated that ARA impairs the viability and hatchability of S. mansoni eggs ex vivo (El Ridi, personal communication) and may well be responsible for parasite ovum attrition in the liver and small intestine via accumulation in the liver, especially in papain-pretreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to examine the basis and mechanism(s) of the anti-schistosomiasis protective effect of cysteine peptidases, particularly the role of thymus (T)-derived lymphocytes and protease enzymatic activity. The experimental model protease papain was used to decipher the effects of cysteine peptidases on parasitological parameters; levels of serum antibody responses; uric acid, a main product of cysteine peptidase catabolic activity [19], [20]; and the endoschistosomicide, arachidonic acid (ARA) [21], [22], [23]. The data together revealed differential effects of the innate and T-dependent immune axis and papain enzymatic activity and structural motifs on S. mansoni worm burden, parasite egg viability, humoral antibody responses, and lung and liver uric acid and ARA levels.…”
Section: Introductionmentioning
confidence: 99%
“…This pioneering study prompted us to examine the relation between susceptibility and resistance of rodents to S. mansoni or S. haematobium infection and ARA levels in serum and lung and liver cells before and weekly after infection. The results strongly suggested that ARA is a potent “natural” schistosomicide, and may be considered an endoschistosomicide [105] .…”
Section: Schistosomicidal Actionmentioning
confidence: 90%